Human Breast Tumour Effect Cells Viability of African Dioscorea rotundata Tuber Extracts in MCF-7 and MDA-MB231 Cell Lines - Odimegwu, Joy (2022)
Objective: We aim to test the efficacy of edible Dioscorea species grown and consumed in Nigeria, Africa on two breast cancer cell lines; MCF-7 and MDAMB231 derived from a luminal and a Triple-Negative Breast Cancer (TNBC) respectively and to confirm safety in non-tumour cells MCF-10A using a wellestablished cytotoxic compound paclitaxel as a standard. Metastatic breast cancer is a prevalent cause of mortality in women around the world. Breast cancer therapies have greatly advanced in recent years, but many patients develop cancer re-occurrence and metastasis and subsequently yield to the disease because of chemoresistance. Methods: Ethanolic extracts of Dioscorea rotundata boiled and raw (DiosB and DiosR) respectively were chemically analyzed for the presence of diosgenin using HPLC and the cytotoxic activities of the extracts were tested on MCF-7, MDA-MB-231 and MCF-10 A cells In vitro by MTT assay. Results: DiosB and DiosR extracts showed a higher maximal effect on MCF-7 cells than on MDA-MB231 after 24 h and 48 h treatments (p<0.0001 and p<0.05 respectively). DiosR, if applied at a range between 50-70 g/ml, can be effective to reduce breast tumor cell viability without affecting non tumorigenic MCF-10 A cells either at 24 h or at 48 h. DiosB showed an IC50 of 38.83 µg/ml while DiosR showed an IC50 of 41.80 µg/ml. Conclusion: These results show that ethanolic extracts of Dioscorea rotundata tubers could be used effectively to treat breast cancer tumors and this is in sync with its diosgenin content as other Dioscorea species applied for similar treatments in Asia and elsewhere.